Bone marrow mesenchymal stem cell-derived small extracellular vesicles promote liver regeneration via miR-20a-5p/PTEN - Zhang, Jing; Gao, Juan; Li, Xianlong; Lin, Dengna; Li, Zhihui; Wang, Jialei; Chen, Junfeng; Gao, Zhiliang; Lin, Bingliang (Frontiers in Pharmacology, 2023)
Balancing hepatocyte death and proliferation is key to non-transplantation treatments for acute liver failure (ALF), which has a high short-term mortality rate. Small extracellular vesicles (sEVs) may act as mediators in the repair of damaged liver tissue by mesenchymal stem cells (MSCs). We aimed to investigate the efficacy of human bone marrow MSC-derived sEVs (BMSC-sEVs) in treating mice with ALF and the molecular mechanisms involved in regulating hepatocyte proliferation and apoptosis. Small EVs and sEV-free BMSC concentrated medium were injected into mice with LPS/D-GalN-induced ALF to assess survival, changes in serology, liver pathology, and apoptosis and proliferation in different phases. The results were further verified in vitro in L-02 cells with hydrogen peroxide injury. BMSC-sEV-treated mice with ALF had higher 24 h survival rates and more significant reductions in liver injury than mice treated with sEV-free concentrated medium. BMSC-sEVs reduced hepatocyte apoptosis and promoted cell proliferation by upregulating miR-20a-5p, which targeted the PTEN/AKT signaling pathway. Additionally, BMSC-sEVs upregulated the mir-20a precursor in hepatocytes. The application of BMSC-sEVs showed a positive impact by preventing the development of ALF, and may serve as a promising strategy for promoting ALF liver regeneration. miR-20a-5p plays an important role in liver protection from ALF by BMSC-sEVs.